Geographic-inquiry on virtual environment mobile application to support fieldwork based on blended learning - Dwi Angga Oktavianto; Sugeng Utaya; Sumarmi Sumarmi; Didik Taryana (Institute of Advanced Engineering and Science, 2024)
Implementing geography learning using the blended learning model is challenging for most geography teachers because this subject is ‘hands-on’ and needs to be learned directly in a real environment using fieldwork. This study aimed to test the pedagogical effectiveness of the geographic-inquiry on virtual environment (GIVE) application in supporting fieldwork based on blended learning to improve students’ geographical thinking. This study used a quasi-experimental method involving 216 high school students from three schools. The paired sample t-test (Sig. 2-tailed 0.000) shows that GIVE has a pedagogical influence on students’ geographical thinking. GIVE also offers a big effect size (Cohen’s d=1.37). The technology and the right smartphone application can help develop a virtual environment close to a real one, so fieldwork and hands-on learning activities can be carried out in blended learning; this helps to increase the quality of geography learning.